GPS RO precipitable water as a possible proxy for rainfall distribution over tropical South America: qualitative analysis - Hierro, Rodrigo Federico (2018)
A principal component analysis (PCA) is applied to radio occultation vertical profiles of water vapor and rainfall data over tropical South America (SA). The low-level flow over this region is climatologically dominated by the Atlantic anticyclone and the trade winds. This results in an inflow of oceanic moist air to the continent from the east, which is forced to lift over the Andes range at the west. Precipitable water data (PW) for the period June 2006–February 2014 derived from the COSMIC/FORMOSAT-3 mission and monthly accumulated rainfall data (R) obtained from Tropical Rainfall Measuring Mission (TRMM) are compared. PCA in modes S and T is performed to find qualitative similarities and differences between both variables. This study shows that specific humidity profiles are able to reproduce a significant amount of the precipitation patterns over tropical SA, as they explain most of the variability during the June 2006–February 2014 period. Therefore, PW may be used as a proxy for rainfall data over the region.